Analisis Pengetahuan Mitigasi Bencana Banjir Bagi Mahasiswa Pendidikan Guru Sekolah Dasar FKIP Universitas Riau - Ophi Fransiska Wantok; Eddy Noviana; Guslinda Guslinda (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2022)
This research is analytical research that aims to describe the knowledge of flood disaster mitigation students of elementary school teacher education at FKIP Riau University. This research is analytical research using descriptive quantitative research. The subjects of this study were fifth-semester students of Elementary School Teacher Education FKIP Riau University. knowledge test about flood disaster mitigation which consists of 12 essay questions. The data analysis technique used by the researcher in this analytical study is a descriptive statistical calculation technique in the form of calculating knowledge test scores 1-4 with very good, good, sufficient, and poor categories, then calculating the percentage value of each knowledge. The results of the overall student disaster mitigation knowledge assessment showed an average of 74.41% in the good category. The results of knowledge based on four indicators are each in the good category.